Fourteen Poems by C. P. Cavafy, chosen and illustrated by David Hockney, translated by Nikos Stangos and Stephen Spender (1966‐67). Issue 2 (1st December 2020) - Butler, Jim
Review of: Fourteen Poems by C. P. Cavafy, chosen and illustrated by David Hockney, translated by Nikos Stangos and Stephen Spender (1966‐67)London: Editions Alecto, Edition A, Folio, illustrated with 12 etchings bound and 1 loose etching, cotton silk boards and silk slipcase, limited edition item